A novel bit scalable leakage model based on genetic algorithm. Issue 18 (24th August 2015) - Zhang, Zhenbin; Wu, Liji; Wang, An; Mu, Zhaoli; Zhang, Xiangmin
Abstract: With the growing popularity of smart integrated circuit (IC) cards, the chip security is attracting more and more attention. Researches on the attack and protection of smart IC cards have become increasingly hot. Side‐channel attack is the practical and effective method, which has brought enormous threat. The efficiency of attack depends on the extent of the leakage model, which characterizes the practical applications. In the power analysis attack, the classical leakage model usually exploits the power consumption of single S‐box, which is called divide and conquer. Taking data encryption standard (DES) algorithm, for example, the attack on each S‐box needs to search the key space of 2 6 in a brute‐force way. In this paper, we propose a novel leakage model, which is more flexible than the classical leakage model. The novel leakage model is based on the power consumption of multiple S‐boxes, and the implementation of this method is combined with genetic algorithm. We can establish leakage model based on the Hamming distance of round output generated by eight S‐boxes in DES algorithm. The experiment verifies the fact that the leakage model of eight S‐boxes can decrease the traces number up to 52% than the classical one based on single S‐box for DES algorithm. It also decreases the traces number up to 32% for SM4 algorithm. All the measurements of power data are acquired from a practical smart IC card. We also conclude that increasing noise, using variable clock, and limiting the lifetime of root key can be the choices of defensive strategy. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The leakage model is based on power consumption of multiple S‐boxes, actually on the Hamming distance of round output from eight S‐boxes, and the implementation of the method is combined with genetic algorithm. The experiment shows that, for data encryption standard algorithm, the leakage model of eight S‐boxes can decrease the trace number up to 52% than the classical one of single S‐box. It also decreases the trace number up to 32% for China SM4 algorithm.